Breathless (first part) how to be a scientific divulger without dying in the attempt - Medina Domínguez, Javier; Robles Carrascosa, Ana (Avances en Supervisión Educativa, 2013)
In the following lines we propose the use of three tools 2.0, free, of disclosure, complementary to each other, and that allow, with little maintenance effort, generate extremely useful documents that are automatically updated and disseminated through the network, actively contributing to the generation of virtual communities of knowledge.